Systematic literature review related to the theoretical knowledge base for non-invasive monitoring of the biomechanical and visco-elastic properties of the myotendinous complex in patients with complete tetraplegia following cervical spinal cord injury - Ana-Andreea Cristea; Aurelian Anghelescu; Gelu Onose (Balneo and PRM Research Journal)
Spinal cord injuries (SCI) are severe injuries of the spine and spinal cord with major consequences on the functionality and quality of life of patients [1,2]. These may include neurological injuries, such as tetraplegia, as well as non-neurological injuries affecting the vertebral structures and adjacent tissues [1,2]. Spinal cord injuries have immense disabling potential, and therapeutic options are limited [3]. Currently, there are no neuroprotective agents [5] to counteract damage or stimulate repair processes following spinal cord trauma. Thus, there is no cure for spinal cord injuries [4].The goal of our doctoral study in which we explore this pathology is to monitor the evolution of the bio-functional parameters of the muscles and tendons of the upper and lower limbs using the MYOTON device, to improve—if necessary—the neuro-recovery programs for tetraplegic patients, lead-ing to more promising results and an improvement in the patient's quality of life. We conducted a comprehensive literature search across multiple databases, following the internationally recognized and evidence-based PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) system. Using the PRISMA reporting system, we entered keywords, as well as keyword syntaxes, into multiple international databases, such as Elsevier, PMC, PubMed, and PEDro, to find relevant articles published between 01.01.2021 and 31.12.2023. As a result of using the PRISMA system, we obtained 91 articles published in English in ISI-indexed journals (Institute for Scientific Information); however, after eliminating duplicates and conducting a screening based on inclusion and exclusion criteria, only 3 articles were found to be relevant to our doctoral study. Nevertheless, the relevance of these articles to our doctoral study is insignificant due to the uniqueness of the topic we are addressing. Moreover, there were multiple knowledge gaps found in the aforementioned studies, such as single-case study limitation, lack of follow-ups, exclusion of spinal cord injury patients, lack of comparison with other rehabilitation methods and lack of clinical guidelines. We hope that through this doctoral study, we will achieve our primary goal, namely, utilizing the MYOTON device to monitor the biofunctional parameters of muscles and tendons, as well as gaining a deeper understanding of the evolving pathophysiology of the myotendinous complex in individuals with complete tetraplegia following spinal cord injury. Achieving our goals will help contribute with new knowledge in the neurorehabilitation field, as well as improve the patient's quality of life and facilitate their socio-professional reintegration.